Diaspora Diplomacy: Emerging Priority of Nepal’s Foreign Policy - Sharma, Pratima (Journal of Political Science, 2021)
Many people from Nepal are currently living in foreign countries. Their living has become a prominent issue in foreign policy and international relations as it has a broader impact on the bilateral connection between Nepal and the host countries as well as in the development back home. Appropriately mobilizing diverse potential inheritance in the Nepali diaspora can be a real boon for Nepal in achieving the national goals. The government is working on that by devising various policies, but the results are not satisfactory. Rigorous homework is yet to be done at the policy-making level to maximize achievements through the effective conduction of diaspora diplomacy. Hence, shedding light on the broader perspective of the Nepali diaspora, this paper attempts to focus on their role in the social, economic and cultural development of Nepal. The new institutional and policy arrangements that policymakers should adopt in upcoming days to address diaspora needs and to maintain a balanced relation between the government and Nepali community residing outside the border are also discussed. The article is descriptive and analytical in format, and the data are collected from secondary sources.